1994
DOI: 10.1007/bf00269493
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-immunoreactive climbing fibres in the cerebellar cortex of the rat

Abstract: The climbing fibre system, one of the two main excitatory inputs to the cerebellar cortex, is anatomically and physiologically well characterized, while the nature of its neurotransmitter is still a matter of debate. We wished to determine whether glutamate-immunoreactive profiles with the morphological characteristics of climbing fibres could be found in the rat cerebellar cortex. For this purpose, a monoclonal 'anti-glutamate' antibody has been used in combination with a sensitive postembedding immunoperoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
10
0
1
Order By: Relevance
“…The use of postembedding immunogold methods for electron microscopy has shown that parallel fiber and climbing fiber synaptic terminals contain high levels of the neurotransmitter glutamate (Somogyi et al, 1986;Grandes et al, 1994a). The release of glutamate from these synaptic terminals in the molecular layer results in the activation of glutamate receptors located on the dendritic tree of Purkinje cells.…”
mentioning
confidence: 99%
“…The use of postembedding immunogold methods for electron microscopy has shown that parallel fiber and climbing fiber synaptic terminals contain high levels of the neurotransmitter glutamate (Somogyi et al, 1986;Grandes et al, 1994a). The release of glutamate from these synaptic terminals in the molecular layer results in the activation of glutamate receptors located on the dendritic tree of Purkinje cells.…”
mentioning
confidence: 99%
“…Numerous silver-intensified gold particles were associated with membranes of axons, synaptic terminals and dendritic spines. Strong Kv3.1b labeling was detected in presynaptic varicosities of parallel fibers characterized by containing round synaptic vesicles and forming asymmetrical synapses with Purkinje cell dendritic spines (Palay and Chan-Palay 1974;Grandes et al 1994) (Fig. 1a-d).…”
Section: Resultsmentioning
confidence: 94%
“…2a-f). Kv3.1b and Kv3.3 were not observed in climbing fiber synaptic boutons identified as bulbous varicosities or as more elongated profiles containing numerous round and electron-translucent synaptic vesicles clustered at synaptic junctions (Palay and ChanPalay 1974;Grandes et al 1994). No specific staining was detected in sections processed without primary antiserum or whenever the primary antiserum was substituted by goat serum.…”
Section: Resultsmentioning
confidence: 95%
“…GluA2/3 is rarely found in non-synaptic membranes (Bergersen et al, 2005) which may lead to speculate that the cellular distribution of GluA2/3 in the cultured cerebellum is at sites of active glutamatergic synapses. Actually, the only remaining glutamatergic presynaptic elements in the molecular layer are the parallel fibres, as the climbing fibres (Grandes et al, 1994b) were cut off during tissue culturing. Also, glutamatergic synapses in the granule cell layer may come from UBCs as they are the sole remaining glutamatergic input in this layer after the loss of the mossy fibre system.…”
Section: Discussionmentioning
confidence: 99%